SOCIO-PSYCHOLOGICAL FACTORS INFLUENCING THE FORMATION OF ATHLETES’ PSYCHOLOGICAL AND EMOTIONAL STATES IN EMERGENCY SITUATIONS (Eureka Journal of Humanities and Social Research, 2026)
This article examines the socio-psychological factors influencing the formation of athletes’ psychological and emotional states in emergency situations. The study analyzes theories of stress, motivation, adaptation, and emotional stability within the field of sports psychology. A review of scientific literature indicates that stress in athletic performance is associated with biological, cognitive, and socio-psychological factors (11). Furthermore, coach–athlete relationships, team environment, motivation levels, and social support were identified as key determinants of athletes’ psychological resilience (6, 7). The findings highlight the necessity of a comprehensive approach to enhancing athletes’ psychological preparedness in emergency situations.
Keywords: Sports psychology, stress, emotional stability, emergency situations, motivation, athlete psychology, adaptation, burnout.